AVALIAÇÃO DA ACEITAÇÃO DO PORTAL INOVAÇÃO: UM ESTUDO DE CASO - Costa, érico da Silva (2012)
This research presents a case study aimed to analyze the acceptance of Innovation Portal, identifying the predictors of behavioral intention to use and usage behavior of drivers of technology adoption by users via extension of the Unified Model of Technology Acceptance, called by Acronym UTAUT (Unified Theory of Acceptance and Use of Technololgy) of Venkatesh et al. (2003). The object of the research Innovation Portal was developed by the Ministry of Science, Technology and Innovation (MCTI) in partnership with the Center for Strategic Studies and Management (CGEE), Brazilian Association for Industrial Development (ABDI) and Instituto Stela, to meet demands the National System of Science, Technology and Innovation (SNCTI) in the country to achieve the proposed objectives, we used qualitative approaches, which was subsidized by the case study method (Yin, 2005) and quantitative methodology supported by UTAUT, applied the portal users and contemplated the result of 264 respondents validated. As for material analysis, we used the literature on electronic government (e-Gov), Internet, National Innovation System, models of technology acceptance, official data and laws pertaining to public sector innovation. The quantitative analysis technique employed was the use of structural equation modeling based on the algorithm PLS (Partial Least Square) with 1000 bootstrap resampling. The main results showed high predictive significance and magnitude of the Behavioral Intention of Use Portal by factors: Expected Performance and Social Influence. Besides demonstrating that the facilitating conditions impacting significantly on the behavior of users of Use. The main conclusion of this study is that we consider the acceptance of a government portal in which the adoption is voluntary, the social factor is highly influential in the intention to use the technology as well as aspects related to user productivity and the consequent sense utility, plus the ease of interaction and domain tool. Such findings ensejam new perspectives in research and studies in the field of e-Gov actions, as well as in directing proper planning, monitoring and evaluation of government projects.